How computerisation is transforming jobs: Evidence from the Eurofound's European Working Conditions Survey - Martina Bisello; Eleonora Peruffo; Enrique Fernandez-Macias; Riccardo Rinaldi (European Commission, Joint Research Centre (JRC), 2019)
This paper investigates changes in the task content, methods and tools of European jobs from 1995 to 2015. Drawing on the taxonomy of tasks proposed by Bisello and Fernández-Macías (2016), this work tries to better understand whether changes in the average intensity of tasks performance are the result of changes in the shares of employment across jobs, or changes in the task content within-jobs, or both. The main findings from a combined analysis of the European Working Conditions Survey (EWCS) and European Jobs monitor data (EJM) suggest that jobs with more social task content expanded relative to the rest, but this is in contrast with a decline in the amount of social tasks people actually do in those (and other) jobs over the same period. A similar contradictory trend can be observed in terms of routine tasks, with compositional and intrinsic changes going in opposite directions: an actual increase in the total levels of routine at work is recorded, notwithstanding marginal compositional declines. The implications of these findings in the context of the current debate on the impact of technological change on employment are discussed.
Keywords: 330; Tasks; Technical Change; Structural Change; Labour Markets; Europe; Occupations